(untitled) (Journal of the College of Basic Education, 2026)
This study explores the Baghdadi School of Hadith as one of the most prominent scholarly traditions that contributed to the establishment and development of critical methodology in Hadith sciences during the 2nd and 3rd centuries AH. Adopting a historical-analytical approach, the research examines the efforts of Baghdadi scholars in scrutinizing both the chain of transmission and the textual content of Hadith, highlighting their methodological standards in verifying reports. It also underscores the role of this school in laying the foundations of Hadith criticism and in advancing criteria for distinguishing between authentic and weak narrations, making it a pivotal reference in the evolution of Hadith studies in subsequent centuries.